Activation of the ankle musculature during the layup gesture in basketball players with chronic ankle instability, a case control study - María Benito-de-Pedro; Raquel Delgado-Delgado; Ángela Aguilera-Rubio; Elena Sonsoles Rodríguez-López; Juan Nicolás Cuenca-Zaldívar; Maura Jiménez-Herranz; Ana Isabel Benito-de-Pedro (PLoS ONE, 2025)
Lateral ankle sprain (LAS) is a very common injury in the world of basketball. Its recurrence rate is very high, generating chronic ankle instability (CAI), accompanied by decreased muscle activation in the ankle musculature and lack of motor control. The aim is to assess the difference in the activation and the moment of greatest solicitation of the peroneus during the development of the layup basketball gesture and to assess the motor control at this moment of greatest solicitation, in patients suffering from CAI and in those who do not suffer from it. In this case-control study, a surface electromyography (sEMG) was conducted in the peroneus lateralis longus (PLL) and peroneus lateralis brevis (PLB) musculature during the layup gesture, on 58 female basketball players, 29 with and 29 without CAI. The presence of significant differences in the group: measurement interaction was found in the variables left PLL RMS left-hand layup and right PLL maximum peak left-hand layup (X 2 (6)=22.246, p = 0.001, X 2 (6)=12.99, p = 0.043) respectively, where higher normalized activation values are observed in CAI group. The post hoc test shows systematically higher percentage values in the CAI group (normalized results with MVC) and higher mean activity of peroneal muscle in patients without CAI. The greatest solicitation of activity in the layup gesture occurs in the impulse prior to the jump. The post hoc test shows systematically higher percentage values in the CAI group, results which non remain throughout the trials. The percentage of activation in the left PLL maximum peak right-hand layup is higher in the non CAI group with a large effect size in single measurements. In relation to motor control, a higher overall signal dispersion is observed in CAI group there is evidence of worse motor control.